Automatic die design and fatigue life prediction of forming die using AI technique: Expert System - Bhatt, MR; Mehta, H; Buch, SH (International Journal of Computer Sciences and Engineering, 2025)
Sheet metal forming is an important process which causes some changes in the shape of solid metal parts via plastic (permanent) deformation. When deliberating with sheet metal forming process in this scenario, die and punch cost plays a vital role, making the processes costlier in whole production cycle. It is required to estimate the die life because it is repeatedly used in manufacturing process. Approximate calculation of fatigue life of axisymmetric forming dies helps in planning for the production. This is calculated using AI technique Expert system. In present research work, the development of expert system has been done using VB, python and AutoCAD environment. The developed ES is enabling to generate manufacturing drawing of the designed die which requires few input parameters. Based on few input parameters, ES predict the fatigue life of these dies during deep drawing forming operations.